Prevention of corruption act, 1988 - Sanjeev, Muthuswamy Brinda (Chennai Swamy, 2023)
This Act as promulgated in 1988 makes the anti-corruption laws more effective by widening their coverage and by strengthening the provisions. The Act incorporates all amendments to the previous Prevention of Corruption Act
Keywords: Bare Act